A solid bath composition containing a timing function unit and a method of making and using the same

CN122997972APending Publication Date: 2026-10-30黄妙仙
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611288349.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]本申请提供了一种含时序功能单元的固体沐浴组合物及其制备方法和使用方法,以解决背景技术中提到的产品释放过快、时序混乱及储存稳定性差的问题

Benefits of technology

1、时序释放精准可控:通过构建包衣厚度梯度与空间位置梯度的双重协同机制,利用表层至内层的渗透路径差异,结合0.005mm~0.30mm的包衣厚度差及≤2mm/≥5mm的深度分布设计,成功实现了功能组分的分阶段有序释放,显著延长了沐浴过程的趣味性与沉浸感。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122997972A_ABST
    Figure CN122997972A_ABST
Patent Text Reader

Abstract

The application discloses a solid bath composition containing a time sequence functional unit and a preparation method and use method thereof, the composition comprising a base composition and a time sequence functional unit; the time sequence functional unit comprises a first type and a second type, both having a functional core and a controlled release coating layer, and utilizing the synergistic effect of water / steam permeation path difference and coating delay parameter to realize accurate time sequence release. Experiments show that the first type unit starts in 5s-30s after water contact, the second type unit starts in 1min-5min, and the time difference is greater than or equal to 30s; at the same time, the hydrophobic coating with a water contact angle greater than or equal to 90 degrees and the low moisture base with a moisture content less than or equal to 8% make the product weight gain rate less than or equal to 1.1% under 40 DEG C / 75%RH accelerated test, solve the problems of existing product release instant, shelf instability and coating easy to damage, realize the multi-stage immersive experience of visual, olfactory, tactile and temperature sensation, and are suitable for bathtub, shower and gas phase fumigation scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of bath product technology, and in particular to a solid bath composition containing a time-sequential functional unit, and its preparation method and usage method. Background Technology

[0002] Existing solid bath products (such as bath salt balls and shower diffusers) typically mix functional particles directly into the matrix. Because these functional particles lack differentiated release control, they are often released synchronously and instantaneously upon contact with water, resulting in an experience concentrated in the first 30 seconds and failing to cover the entire bathing process. Simultaneously, exposed functional components (especially gas-generating components and fragrances) are susceptible to erosion from matrix moisture and environmental humidity, leading to moisture absorption, softening, and premature deterioration during storage. While some technologies attempt to incorporate coating methods, most focus only on coating thickness, neglecting to achieve precise, sequential release through the coordinated control of coating parameters and spatial distribution, resulting in a limited product experience and insufficient stability. Summary of the Invention

[0003] This application provides a solid bath composition containing a timing functional unit, as well as its preparation and usage methods, to solve the problems of excessively rapid product release, disordered timing, and poor storage stability mentioned in the background art.

[0004] In order to solve the above-mentioned technical problems, in a first aspect, this application provides a solid bath composition containing a time-sequential functional unit, comprising a matrix composition and a time-sequential functional unit dispersed or disposed in the matrix composition; The timing functional unit includes at least two types of timing functional units with different release delay parameters, and the timing functional unit includes a functional core and a controlled release coating. When in contact with water, shower water flow, carrier mist, hot steam, or the gas phase contact path of a gas phase release device under bathing or fumigation conditions, at least two types of timing functional units have different release delay parameters so that the timing functional units release in stages during the bathing or fumigation process.

[0005] In one embodiment, the matrix composition comprises 70 to 99 parts by weight, and the timing functional unit comprises 1 to 30 parts by weight.

[0006] In one embodiment, the controlled-release coating is one or more of an immediate-release coating layer, a sustained-release coating layer, or a composite coating layer; The immediate-release coating layer is selected from one or more of the following water-soluble materials that are solid at room temperature: hydroxypropyl methylcellulose, polyvinyl alcohol, or polyethylene glycol with a molecular weight of 4000 or higher. The sustained-release coating layer is selected from one or more of the hydrophobic materials ethyl cellulose, stearic acid, beeswax or shellac, and the water contact angle of the sustained-release coating layer is ≥90°; The composite coating layer comprises a hydrophobic inner layer and a swollen outer layer from the inside out. Specifically, the composite coating layer has a concentric double-layer structure, with the hydrophobic inner layer and the swollen outer layer stacked sequentially from the inside out, centered on the geometric center of the functional core. The hydrophobic inner layer is directly bonded to the outer surface of the functional core, and the swollen outer layer covers the outside of the hydrophobic inner layer and is in direct contact with the matrix composition. There is no additional transition layer or adhesive interface layer between the two layers, forming a continuous gradient coating structure. In addition, by controlling the thickness ratio of the hydrophobic inner layer to the swollen outer layer within the range of 1:3 to 3:1, the hydrophobic layer can be used to delay the initial water penetration, while the microporous channels formed after the outer layer swells can be used to control the later release rate, avoiding premature disintegration or excessive retardation of the coating.

[0007] In one embodiment, the timing functional unit includes a first type of functional unit and a second type of functional unit. When in contact with water or hot steam, the first type of functional unit is activated and released within 5s to 30s, and the second type of functional unit is activated and released within 1min to 5min, forming a phased sensory feedback.

[0008] In one embodiment, the first type of functional unit is disposed on the surface or edge region of the matrix composition, at a depth of ≤2mm from the surface; The second type of functional unit is disposed in the inner layer, central region or embedded in the deep layer of the matrix composition, at a depth ≥5mm from the surface.

[0009] This application leverages the differences in the permeation pathways from the surface to the inner layers of the matrix, combined with the differences in the delay parameters of the controlled-release coating layers, to achieve the time-sequential release of functional components.

[0010] In one embodiment, the controlled-release coating thickness of the first type of functional unit is 0.005 mm to 0.100 mm, the controlled-release coating thickness of the second type of functional unit is 0.05 mm to 0.30 mm, and the controlled-release coating thickness of the first type of functional unit is less than the controlled-release coating thickness of the second type of functional unit.

[0011] In one embodiment, the functional core comprises one or more of a gas-generating component, a fragrance component, a color-developing component, a temperature-sensitive component, or a skin-care component. Specifically, the gas-generating component is a mixture of sodium bicarbonate and an organic acid, with a mass ratio of sodium bicarbonate to organic acid of 1:0.8 to 1:1.2; the fragrance component is a plant essential oil or a microcapsule fragrance, wherein the wall material of the microcapsule fragrance is gelatin-gum arabic, and the core material addition amount is 0.5 to 2 wt%; the temperature-sensitive component includes 0.1% to 0.5% menthol (cooling sensation) or 0.05% to 0.2% capsaicin / ginger root extract (warming sensation); the color-developing component is selected from pH-responsive natural anthocyanins or food-grade pigments; the skin-care component is selected from inert moisturizers or liposome encapsulations that do not react with the sodium bicarbonate / organic acid system. All of the above components are commonly used raw materials in the art that can achieve solid particle molding and are compatible with the coating system.

[0012] In one embodiment, the matrix composition is one of an effervescent bath salt matrix, a sustained-release shower aromatherapy matrix, or a gel tablet matrix; The effervescent bath salt matrix has a moisture content of 1% to 8%, a pH value of 5.5 to 7.5, and a hardness of 2 kg / cm² to 5 kg / cm². The slow-release shower fragrance matrix has a moisture content of 3% to 8%, a pH value of 6.0 to 7.5, and a hardness of 1 kg / cm2 to 4 kg / cm2. The moisture content of the gel tablet matrix is ​​2% to 5%, the pH value is 6.0 to 7.5, and the hardness is 4 kg / cm2 to 6 kg / cm2.

[0013] It should be noted that the effervescent bath salt matrix includes 55-70 parts sea salt or magnesium sulfate, 15-25 parts sodium bicarbonate, 10-20 parts citric acid, and 2-5 parts polyethylene glycol-6000; the sustained-release shower aromatherapy matrix includes 2-4 parts gelatin, 10-25 parts β-cyclodextrin, 3-5 parts glycerin, and 0.5-2 parts plant essential oil; the gel tablet matrix includes 55-95 parts sucrose, 2-5 parts polyethylene glycol-6000, 0.5-2.5 parts sodium carboxymethyl cellulose, and 0.5-1 part magnesium stearate.

[0014] In addition to the three types of substrates mentioned above, other solid compressible substrates with similar moisture content control capabilities and mechanical strength can also achieve the effects of this application when used in conjunction with the timing functional units.

[0015] Secondly, this application also provides a method for preparing a solid bath composition containing a time-sequential functional unit as described above, comprising the following steps: Preparation of functional core: The gas-generating component, fragrance component or temperature-sensing component is made into core particles with a particle size of 0.1 mm to 5 mm by wet granulation, extrusion spheroidization or spray drying. Controlled-release coating treatment: The core is coated using fluidized bed spray coating, roller coating, or microencapsulation to form a first type of immediate-release unit and a second type of sustained-release unit; wherein, the inlet air temperature of the fluidized bed spray coating is 40℃~50℃, the atomization pressure is 0.15MPa~0.3MPa, the spraying speed is 5mL / min~15mL / min, and the liquid-solid content of the coating is 5%~15%; Matrix mixing and molding: First, add 60%–80% of the total dry matrix powder to the mixer, then add the timing function unit and mix at a low speed of 8–15 rpm for 3–8 minutes. Next, add the remaining dry matrix powder for a second covering and mixing. After passing through a 10–20 mesh sieve, press or mold the mixture under a pressure of 5 kN–20 kN. Control the mold temperature during pressing to ≤40℃. The resulting composition has a density of 1.2 g / cm³. 3 ~1.5g / cm 3 ; Post-processing: Dry at below 40℃ until moisture content ≤8%, then package.

[0016] In one embodiment, the controlled-release coating process further includes a step of preparing a composite coating layer: The composite coating layer consists of a hydrophobic inner layer and a swollen outer layer stacked sequentially from the inside out; The steps for preparing the composite coating layer are as follows: first, an ethyl cellulose ethanol solution is sprayed onto the functional core to form the hydrophobic inner layer, and then an aqueous solution of hydroxypropyl methyl cellulose is sprayed onto the outside of the hydrophobic inner layer to form the swollen outer layer. The total thickness of the two layers is controlled between 0.01 mm and 0.30 mm, and the thickness ratio of the hydrophobic inner layer to the swollen outer layer is 1:3 to 3:1.

[0017] Thirdly, this application also provides a method of using the solid bath composition containing the time-sequential functional unit as described above. The method of use is to use the solid bath composition in a bath, shower or fumigation setting, and to use it in conjunction with water, shower water flow, carrier mist, hot steam or gas phase release device to achieve multi-stage sensory release.

[0018] The beneficial effects of this application are: 1. Precise and controllable release in sequence: By constructing a dual synergistic mechanism of coating thickness gradient and spatial position gradient, and utilizing the difference in penetration path from the surface to the inner layer, combined with a coating thickness difference of 0.005mm to 0.30mm and a depth distribution design of ≤2mm / ≥5mm, the functional components are successfully released in stages and in an orderly manner, significantly extending the fun and immersive experience of the bathing process.

[0019] 2. Excellent shelf stability: By using hydrophobic materials with a water contact angle ≥90° to construct the controlled-release coating layer and strictly controlling the moisture content of the matrix composition to ≤8%, an efficient moisture barrier is built between the functional core and the external environment, improving shelf stability.

[0020] 3. High Process Compatibility and Yield: By adopting a feeding strategy of "adding most of the dry powder first, then adding functional units, low-speed mixing, and secondary coating," and limiting the mold temperature during the pressing process to ≤40℃, the mechanical wear and heat melting risks of the functional units during molding are minimized. This process ensures the integrity of the coating structure, making the release behavior of the final product strictly follow the preset timing logic, and possesses good feasibility for industrial production. Furthermore, the composition density is controlled at 1.2 g / cm³. 3 ~1.5g / cm 3 Within a certain range, the porosity of the matrix and the water vapor permeation rate can be balanced. If the density is too low, it will easily lead to rapid disintegration and shorten the time sequence. If the density is too high, it will hinder the permeation of steam into the inner layer. This parameter, together with the coating thickness and spatial position, constitutes the physical basis for time sequence regulation.

[0021] 4. Rich Multi-Sensory Experience: Through time-series control, it achieves the phased delivery of multi-dimensional sensory feedback such as vision (color development / bubbles), hearing (popping sound), smell (fragrance), and touch (cooling / warming), which meets consumers' needs for personalized and immersive bathing experience. Moreover, the product form is suitable for various application scenarios such as tub bath, shower and vapor fumigation. Attached Figure Description

[0022] Figure 1 This is a phased release curve diagram of the first type of functional unit and the second type of functional unit in the embodiments of this application; Figure 2 This is a graph showing the weight gain rate of different samples under accelerated testing conditions in the embodiments of this application. Detailed Implementation

[0023] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, the specific embodiments of this application are described in detail below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of this application. However, this application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of this application. Therefore, this application is not limited to the specific embodiments disclosed below.

[0024] As used herein, the terms “prepared from” and “comprising” are synonymous. The terms “comprising,” “including,” “having,” “containing,” or any other variations thereof, as used herein, are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.

[0025] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1 to 5” is disclosed, the described range should be interpreted as including the ranges “1 to 4”, “1 to 3”, “1 to 2”, “1 to 2 and 4 to 5”, “1 to 3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.

[0026] Furthermore, the indefinite articles “a” and “an” preceding the elements or components of this application do not impose any limitation on the quantity requirement (i.e., the number of times) of the elements or components. Therefore, “an” or “a” should be interpreted as including one or at least one, and the singular form of an element or component also includes the plural form, unless the quantity clearly refers to the singular form.

[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0028] In this application, the time-sequential functional units have a core-shell structure, with the functional core located at the core position and the controlled-release coating layer uniformly covering the outer periphery of the core. In the matrix composition, the first type of functional units are mainly distributed in the low-resistance region near the surface (depth ≤ 2 mm), while the second type of functional units are embedded in the high-resistance region (depth ≥ 5 mm) by the matrix material. This synergy between the core-shell structure and the spatial gradient distribution constitutes the physical basis for time-sequential release.

[0029] It should be noted that the materials such as hydroxypropyl methylcellulose, polyvinyl alcohol, ethyl cellulose, and beeswax mentioned in this application are only representative examples and not an exhaustive list. Any polymeric material with a corresponding water solubility rate (complete dissolution time in water ≤30s for immediate-release types) or hydrophobic properties (water contact angle ≥90°) can replace the aforementioned materials to achieve the controlled-release coating layer of this application. Any active ingredient possessing gas-generating, fragrance, temperature-sensing, or skin-care functions and stable in a matrix with pH 5.5–7.5 and moisture content ≤8% can be used as a material for the functional core. Based on the principle of coating thickness gradient and spatial synergy disclosed in this application, those skilled in the art can reasonably expect that the above-mentioned equivalent alternatives can all achieve the technical effect of phased sensory feedback.

[0030] Example 1: Time-sequence bursting bath salt balls 1. Formula (parts by weight): ① Matrix composition (effervescent bath salt matrix): 60 parts sea salt, 20 parts sodium bicarbonate, 15 parts citric acid, 3 parts polyethylene glycol-6000, and 2 parts polysorbate-80.

[0031] Physical properties: Moisture content 5%, pH 6.5, hardness 3.5 kg / cm² 2 .

[0032] ② Timing Functional Units (15 in total): The first type of functional unit (immediate-release type, 8 portions): The functional core is a gas-generating complex with a particle size of 1 mm. The gas-generating component of the gas-generating complex is a mixture of sodium bicarbonate and organic acid, with a sodium bicarbonate:citric acid ratio of 1:1. The controlled-release coating layer is water-soluble hydroxypropyl methylcellulose with a thickness of 0.02 mm. It is set on the surface of the spheres with a depth ≤1 mm.

[0033] The second type of functional unit (slow-release type, 7 portions): The functional core consists of a gas-generating complex and a blue food coloring, with a particle size of 1 mm; the controlled-release coating layer is ethyl cellulose with a thickness of 0.10 mm. It is set in the inner layer of the sphere with a depth ≥ 8 mm.

[0034] 2. Preparation method: S1. Core preparation: Sodium bicarbonate and citric acid are passed through an 80-mesh sieve, mixed evenly, and 5% PVP ethanol solution is used as a binder. The mixture is then granulated into particles with a diameter of 1 mm by a wet granulation machine and dried at 40°C.

[0035] S2. Coating treatment: Fluidized bed coating is used.

[0036] The first type of functional unit: spraying in 5% hydroxypropyl methylcellulose aqueous solution, with an inlet air temperature of 45℃, an atomization pressure of 0.2MPa, a spraying speed of 10mL / min, and obtaining a thickness of 0.02mm.

[0037] The second type of functional unit: spraying in 5% ethyl cellulose ethanol solution, with an inlet air temperature of 40℃, an atomization pressure of 0.2MPa, a spraying speed of 8mL / min, to obtain a thickness of 0.10mm.

[0038] The coating thickness was measured using a micrometer, with 50 particles randomly sampled and the average value taken.

[0039] S3. Mixing and Molding: Mix sea salt, sodium bicarbonate, citric acid, and PEG-6000 evenly; then, take 70% of the mixed dry powder and put it into a three-dimensional motion mixer, add the timing function unit, mix at 8 rpm for 5 minutes, then add the remaining 30% dry powder and mix for 3 minutes, then pass through a 16-mesh sieve; finally, take 50g of material and place it in a spherical mold, press it with 10kN pressure, and control the mold temperature below 35℃.

[0040] S4. Post-processing: Dry in a 35℃ oven until the moisture content is ≤5%, remove and cool, then seal in heat shrink film.

[0041] 3. Performance: The obtained product was placed in water at 37°C. At the 8th second, the first type of functional unit on the surface ruptured, producing dense bubbles and bursting sounds and white foam, which lasted for about 30 seconds. At the 90th second, the second type of functional unit in the inner layer broke through the coating, releasing blue pigment and continuing to produce gas until the 5th minute. No coating fragments remained throughout the process.

[0042] Example 2: Step-release aromatherapy tablets 1. Formula (parts by weight): ① Matrix composition (slow-release shower aromatherapy matrix): 15 parts β-cyclodextrin, 3 parts gelatin, 4 parts glycerin, 1.5 parts lavender essential oil, and the balance of sucrose.

[0043] Physical properties: Moisture content 6%, pH 6.8, hardness 2.5 kg / cm² 2 .

[0044] ② Timing Functional Units (10 in total): The first functional unit (immediate-release type, 4 portions): the functional core is menthol with a particle size of 0.5 mm; the controlled-release coating layer is polyethylene glycol-4000 with a thickness of 0.01 mm, located at the edge of the tablet.

[0045] The second functional unit (sustained-release type, 6 portions): The functional core is a lavender essential oil microcapsule with a gelatin-gum arabic wall material and a particle size of 0.2 mm; the controlled-release coating layer is a composite coating, with an inner layer of ethyl cellulose (0.03 mm thick) and an outer layer of hydroxypropyl methylcellulose (0.06 mm thick), for a total thickness of 0.09 mm. It is located in the center of the tablet with a depth ≥6 mm.

[0046] 2. Preparation method: S1. Core fabrication: First functional unit: molten menthol spray condenses into 0.5mm particles.

[0047] The second type of functional unit: microcapsules prepared by coagulation of lavender essential oil and gelatin-gum arabic.

[0048] S2. Coating treatment: First functional unit: Roll coating method for coating molten polyethylene glycol-4000.

[0049] The second type of functional unit: fluidized bed coating, first sprayed with 5% ethyl cellulose-ethanol solution at an inlet air temperature of 40℃, then sprayed with 8% hydroxypropyl methyl cellulose aqueous solution at an inlet air temperature of 45℃.

[0050] S3. Mixing and molding: Mix the dry powder of the matrix, add the timing unit, mix at low speed, and finally add the essential oil so that the essential oil is adsorbed on the carrier and pressed into a disc with a diameter of 6cm and a pressure of 8kN.

[0051] S4. Post-processing: Low-temperature drying, aluminum foil bag packaging.

[0052] 3. Performance: When the prepared product is placed under a shower, the first type of functional unit melts in the 5th second, releasing a cooling sensation; in the 70th second, the outer layer of the second type of unit, hydroxypropyl methylcellulose, swells and disintegrates, continuously releasing a lavender aroma that lasts for more than 10 minutes without any sudden release.

[0053] Example 3: Thermal aromatherapy blocks for vapor-phase fumigation 1. Formula (parts by weight): ① Matrix composition (gel tablet matrix): 20 parts microcrystalline cellulose, 2 parts sodium carboxymethyl cellulose, 1 part xanthan gum, 0.8 parts magnesium stearate, 3 parts glycerin, and appropriate amount of water.

[0054] Physical properties: Moisture content 3.5%, pH 6.5, hardness 5.0 kg / cm² 2 .

[0055] ② Timing Functional Units (5 in total): Class 1 functional unit (immediate-release type, 2 portions): The functional core is composed of red pigment and ginger root extract, with a particle size of 1.5 mm; the controlled-release coating layer is composed of polyvinyl alcohol, with a thickness of 0.05 mm.

[0056] The second type of functional unit (sustaining-release type, 3 parts): the functional core is ginger essential oil microcapsules with a particle size of 3mm; the controlled-release coating layer is beeswax with a thickness of 0.20mm.

[0057] 2. Preparation method: S1. Core preparation: Ginger root extract and pigment are mixed and granulated, and ginger essential oil is made into β-cyclodextrin inclusion complex.

[0058] S2. Coating treatment: Category 1: Coating with polyvinyl alcohol aqueous solution.

[0059] Category 2: Beeswax hot melt coating, roller temperature is 50℃.

[0060] S3. Mixing and molding: After the dry powder is mixed, it is incorporated into the functional unit. The mixing speed is controlled at 5 rpm and the mixing time is shortened to 2 minutes to prevent wear on the beeswax layer. Finally, it is pressed and molded under a high pressure of 15 kN.

[0061] S4. Post-processing: Drying and packaging.

[0062] 3. Performance: Place the prepared product at the air outlet of the steam fumigation device. After 15 seconds, the surface turns red and releases a warm sensation, raising the body surface temperature by 2°C. After 2 minutes, the interior releases a ginger aroma, accompanied by a continuous warm sensation, making it suitable for sauna or facial fumigation scenarios.

[0063] Comparative Example 1: Uncoated The formula is the same as in Example 1, except that the functional units are not coated.

[0064] Results: After being placed in water, all the particles burst and released simultaneously within 5 seconds, producing a large amount of foam instantly before the reaction stopped, making it impossible to create a sequential experience. Furthermore, after one month of storage, the particles absorbed moisture severely, making them difficult to compress.

[0065] Comparative Example 2: Single-layer coating The formulation is the same as in Example 1, except that both the first and second functional units are coated with ethyl cellulose of the same thickness.

[0066] Result: The release time difference between the first type of functional unit and the second type of functional unit is only 10 seconds, which cannot meet the long timing requirements and results in overlapping sensory experiences.

[0067] Comparative Example 3: Upper Limit of Coating Thickness The formulation is the same as in Example 1, except that the thickness of the ethyl cellulose coating layer of the second type of functional unit is set to 0.40 mm.

[0068] Results: When the prepared product was placed in water at 37°C, the first type of functional unit on the surface ruptured normally and released bubbles at the 8th second. However, until the end of the 5th minute of observation, no obvious signs of release were observed from the second type of functional unit in the inner layer. The coating layer structure remained intact but did not disintegrate, and no blue pigment or gas was released. This indicates that when the coating thickness exceeds 0.30 mm, the water permeation resistance is too high, causing the second type of functional unit to fail to initiate release within the predetermined time (1 min to 5 min), thus failing to achieve effective timing feedback.

[0069] Comparative Example 4: Upper Limit of Coating Moisture Content The formulation is the same as in Example 1, except that the matrix composition is not completely dried and has a moisture content of 12%.

[0070] Results: During the pressing process, the material exhibited obvious sticking and impaction, and the hardness of the finished product was uneven. After one month of storage, the sample gained 5.5% in weight, and the internal gas-producing components underwent partial pre-reaction, resulting in a sample volume expansion of about 10%. Visible white crystals (sodium citrate) and fine cracks appeared on the surface.

[0071] Comparative Example 5: No gradient formed in spatial location The formulation is the same as in Example 1, except that the spatial distribution of the timing functional units does not form a gradient difference.

[0072] Results: When the prepared product was placed in water at 37°C, some of the second type of functional units were located on the surface, and the coating structure was damaged due to improper mixing process. The second type of units were abnormally released at about 20 seconds, which overlapped with the release time of the first type of units. This resulted in a lack of clear time difference, confused sensory experience, and inability to distinguish the stages.

[0073] Test methods and test data (1) Release timing test A modified rinsing method was used to simulate the bathing process: the sample to be tested was fixed in a constant temperature water bath at 37℃, and the water flow rate was controlled at 500 mL / min. A high-speed camera (200 frames / second) was used to record the start time of bubble generation to determine the gas release time; a UV-Vis spectrophotometer was used to measure the absorbance of the water at a specific wavelength to determine the pigment release concentration.

[0074] like Figure 1 As shown, the first type of functional unit initiates rapid release within 5 to 30 seconds of contact with water, resulting in a steep release curve; the second type of functional unit initiates release within 1 to 5 minutes of contact with water, with extremely slow initial release and a significant hysteresis characteristic. The release start time difference between the two types of units is ≥30 seconds, verifying the effectiveness of the timing control.

[0075] (2) Comparison of phased release behaviors The release behavior of different samples was compared and analyzed. Each group of samples was tested 10 times in parallel. The data are expressed as mean ± standard deviation. The results are shown in Table 1.

[0076] Table 1

[0077] As shown in Table 1, embodiments 1-3 of this application successfully constructed a significant release time difference (65s-105s) by controlling the differences in coating thickness and spatial distribution, achieving a clear multi-stage sensory experience. In contrast, Comparative Example 1 resulted in synchronous release due to the lack of coating; Comparative Example 2 had too small a time difference due to uniform coating thickness, insufficient to counteract spatial disorder; Comparative Example 3 had an excessively thick coating, causing the sustained-release unit to fail to respond on time; and Comparative Example 5 suffered from disordered spatial distribution, resulting in timing chaos. This demonstrates that this application can achieve precise timing control by reasonably setting the coating thickness and spatial position.

[0078] (3) Shelf stability test Accelerated testing was conducted according to the relevant requirements of the "Guidelines for Cosmetic Stability Testing": Samples were placed in a constant temperature and humidity chamber at 40℃±2℃ and 75%±5% relative humidity for one month. After removal, the weight gain, hardness change, and appearance change of the samples were measured. Test results are available in [link to relevant documentation]. Figure 2 And Table 2.

[0079] like Figure 2 As shown, Example 1 (effervescent matrix) had a weight gain of only 0.8% within 4 weeks, and its hardness increased from 3.5 kg / cm². 2 Slightly decreased to 3.4 kg / cm² 2 There was no change in appearance. However, the control group 1 (without coating) had a weight gain of 5.2% and suffered severe moisture absorption and collapse.

[0080] Table 2

[0081] As shown in Table 2, under stringent accelerated testing conditions, Examples 1-3 of this application maintained a weight gain rate below 1.1% over four weeks, with the hardness remaining essentially unchanged. This demonstrates that the synergistic effect of the hydrophobic coating and moisture effectively blocks moisture without softening, whitening, or premature gas generation, exhibiting excellent moisture-proof performance and environmental adaptability. In contrast, Comparative Example 1, lacking coating protection, suffered severe moisture absorption, resulting in a weight gain rate as high as 5.2%, with significant moisture absorption collapse and volume expansion. Comparative Example 4 showed a weight gain rate of 5.5%, with crystal precipitation on the surface, leading to storage failure.

[0082] In summary, this application utilizes the difference in coating thickness combined with the difference in spatial depth to achieve a controllable release time difference of 65s to 105s. Simultaneously, by combining the hydrophobic coating with a low-moisture matrix, it achieves excellent moisture-proof performance with an accelerated test weight gain rate of ≤1.1%. Furthermore, the use of stepwise feeding and low-speed mixing processes ensures coating integrity and mass production feasibility. Through the synergistic effect of coating delay parameters and spatial penetration paths, this application significantly extends the multi-sensory experience of solid bath compositions and effectively improves shelf life.

[0083] The options described in the above method embodiments are also applicable to this embodiment, and will not be detailed here. The remaining content of this application's embodiments can be found in the above method embodiments, and will not be repeated in this embodiment.

[0084] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0085] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A solid bath composition containing a time-sequential functional unit, characterized in that, Includes a matrix composition and timing functional units dispersed or disposed in the matrix composition; The timing functional unit includes at least two types of timing functional units with different release delay parameters, and the timing functional unit includes a functional core and a controlled release coating. When in contact with water, shower water flow, carrier mist, hot steam, or the gas phase contact path of a gas phase release device under bathing or fumigation conditions, at least two types of timing functional units have different release delay parameters so that the timing functional units release in stages during the bathing or fumigation process.

2. The solid bath composition containing a timing functional unit according to claim 1, characterized in that, The matrix composition comprises 70 to 99 parts by weight, and the timing functional unit comprises 1 to 30 parts by weight.

3. The solid bath composition containing a timing functional unit according to claim 1, characterized in that, The controlled-release coating is one or more of an immediate-release coating layer, a sustained-release coating layer, or a composite coating layer; The immediate-release coating layer is selected from one or more of the following water-soluble materials that are solid at room temperature: hydroxypropyl methylcellulose, polyvinyl alcohol, or polyethylene glycol with a molecular weight of 4000 or higher. The sustained-release coating layer is selected from one or more of the hydrophobic materials ethyl cellulose, stearic acid, beeswax or shellac, and the water contact angle of the sustained-release coating layer is ≥90°; The composite coating layer consists of a hydrophobic inner layer and a swollen outer layer from the inside out.

4. The solid bath composition containing a timing functional unit according to claim 1, characterized in that, The timing functional unit includes a first type of functional unit and a second type of functional unit. When in contact with water or hot steam, the first type of functional unit is activated and released within 5s to 30s, and the second type of functional unit is activated and released within 1min to 5min, forming a phased sensory feedback.

5. The solid bath composition containing a timing functional unit according to claim 1, characterized in that, The first type of functional unit is disposed on the surface or edge region of the matrix composition, at a depth of ≤2mm from the surface; The second type of functional unit is disposed in the inner layer, central region or embedded in the deep layer of the matrix composition, at a depth ≥5mm from the surface.

6. The solid bath composition containing a timing functional unit according to claim 4, characterized in that, The controlled-release coating thickness of the first type of functional unit is 0.005 mm to 0.100 mm, the controlled-release coating thickness of the second type of functional unit is 0.05 mm to 0.30 mm, and the controlled-release coating thickness of the first type of functional unit is less than the controlled-release coating thickness of the second type of functional unit.

7. The solid bath composition containing a timing functional unit according to claim 1, characterized in that, The functional core includes one or more of the following: gas-generating components, fragrance components, color-developing components, temperature-sensing components, or skin-care components.

8. The solid bath composition containing a timing functional unit according to claim 1, characterized in that, The matrix composition is one of effervescent bath salt matrix, sustained-release shower aromatherapy matrix, or gel tablet matrix; The effervescent bath salt matrix has a moisture content of 1%–8%, a pH value of 5.5–7.5, and a hardness of 2 kg / cm². 2 ~5kg / cm 2 ; The slow-release shower fragrance matrix has a moisture content of 3%–8%, a pH value of 6.0–7.5, and a hardness of 1 kg / cm². 2 ~4kg / cm 2 ; The moisture content of the gel tablet matrix is ​​2%–5%, the pH value is 6.0–7.5, and the hardness is 4 kg / cm². 2 ~6kg / cm 2 .

9. A method for preparing a solid bath composition containing a time-sequential functional unit as described in any one of claims 1-8, characterized in that, Includes the following steps: Preparation of functional core: At least one of the following components is selected: gas-generating component, fragrance component, color-developing component, temperature-sensing component, skin-care component, cooling component or heat-generating component, and is prepared into a functional core by wet granulation, extrusion spheroidization, spray drying, melt condensation, adsorption granulation or microencapsulation. Controlled-release coating treatment: The core is coated using fluidized bed spray coating, roller coating, or microencapsulation to form a first type of immediate-release unit and a second type of sustained-release unit; wherein, the inlet air temperature of the fluidized bed spray coating is 40℃~50℃, the atomization pressure is 0.15MPa~0.3MPa, the spraying speed is 5mL / min~15mL / min, and the liquid-solid content of the coating is 5%~15%; Matrix mixing and molding: First, add 60%–80% of the total dry matrix powder to the mixer, then add the timing function unit and mix at a low speed of 8–15 rpm for 3–8 minutes. Next, add the remaining dry matrix powder for a second covering and mixing. After passing through a 10–20 mesh sieve, press or mold the mixture under a pressure of 5 kN–20 kN. Control the mold temperature during pressing to ≤40℃. The resulting composition has a density of 1.2 g / cm³. 3 ~1.5g / cm 3 ; Post-processing: Dry at below 40℃ until moisture content ≤8%, then package.

10. A method of using a solid bath composition containing a timing functional unit as described in any one of claims 1-8, characterized in that, The solid bathing composition can be used in bath, shower or fumigation scenarios, in conjunction with water, shower water flow, carrier mist, hot steam or gas phase release devices, to achieve multi-stage sensory release.